Against harmony: progressive and radical Buddhism in modern Japan - Shields, James Mark (Oxford university press, 2017)
The many faces of Meiji Buddhist enlightenment -- Unification and spiritual activism: Murakami and Manshi -- Warp & Woof: the new Buddhist discovery of society -- Zen & the art of treason: renegade priests of late Meiji -- Anarcho-Buddhist utopia: Taisho Tolstoyans -- Extremes meet: radical Buddhists of early Showa